A Case of a Chronic Pancreatic Pseudocyst Causing Atraumatic Splenic Rupture without Evidence of Acute Pancreatitis - P. Moori; E. J. Nevins; T. Wright; C. Bromley; Y. Rado (Case Reports in Surgery)
Atraumatic splenic rupture is a rare complication of a pancreatic pseudocyst (PP), described in the setting of chronic pancreatitis. There is common understanding, within the literature, that an inflammatory process at the tail of the pancreas may disrupt the spleen and result in such splenic complications. The authors present a case report of a 29-year-old male with a PP, associated with chronic pancreatitis. The patient had a history of excessive alcohol intake and presented to the emergency department with a short history of abdominal pain and vomiting. He denied any significant history of trauma and serum amylase levels were normal. An admission computed tomography (CT) scan of the abdomen confirmed the presence of a PP in direct contact with the spleen. The CT also demonstrated a heterogenous hypodense area of the splenic hilum, along with perisplenic fluid. The patient was admitted for observation. His abdominal pain progressed, and he became haemodynamically unstable. An emergency ultrasound scan (USS) at this time revealed intra-abdominal haemorrhage. A subsequent CT confirmed splenic rupture, which was managed surgically with a full recovery. Few such cases are documented within the literature and more understanding of preempting such events is needed.